HUBUNGAN ANTARA MINAT BELAJAR DAN FASILITAS BELAJAR SISWA DENGAN PRESTASI BELAJAR SOSIOLOGI SISWA KELAS XI IPS SMAN 3 SURAKARTA TAHUN PELAJARAN 2013/2014 - Anggraini, Erin (ISSN.2252-8407)
Abstract. Erin Anggraini. K8409022. THE CORRELATION BETWEEN LEARNING INTEREST AND STUDENT?S LEARNING FACILITY WITH SOCIOLOGICAL LEARNING ACHIEVEMENT OF THE STUDENTS OF GRADE XI IPS IN SMA NEGERI 3 SURAKARTA FOR ACADEMICAL YEAR OF 2013/2014. Thesis, Surakarta: Teacher Training and Education Faculty. Sebelas Maret University of Surakarta. Juny. 2013. The aims of the research are to find : (1) The correlation between learning interest with sociological learning achievement, (2) The correlation between student?s learning facility with sociological learning achievement, (3) The correlation between learning interest and student?s learning facility with sociological learning achievement. The research takes place in SMA Negeri 3 Surakarta. The method of the research is correlational research. The population of the research are the whole students of grade XI IPS in SMA Negeri 3 Surakarta for academical year 2013/2014, with the total amount of 120 students. The sample is taken by using random sampling technique as 92 students. The principal data collecting is done by using questionnaire. The data analysis technique used was statistical multiple regression analysis technique. Based on the result of the research, it can be concluded that : (1) There is  significant correlation between learning interest with sociological learning achievement of the students of grade XI IPS in SMA Negeri 3 Surakarta for academical year 2013/2014. It can be seen from the data analysis result which showed rx1y = 0,477, and p = 0,000. (2) There is significant correlation between student?s learning facility with sociological learning achievement of the students of grade XI IPS in SMA Negeri 3 Surakarta for academical year 2013/2014. It can be seen from the data analysis result which showed rx2y = 0,760, and p = 0,000. (3) There is significant correlation between learning interest and student?s learning facility with sociological learning achievement of the students of grade XI IPS in SMA Negeri 3 Surakarta for academical year 2013/2014. It can be seen from the data analysis result which showed R = 0,768, p = 0,002 and F = 63,808. Keywords: interests, facilities, learning achievement